Applications of Hydrogels in Premature Ovarian Failure and Intrauterine Adhesion - Zhang, Donghai; Ding, Chuanfeng; Duan, Tao; Zhou, Qian (Frontiers in Materials, 2022)
Premature ovarian failure (POF) and intrauterine adhesion (IUA), which easily lead to reduced fertility in premenopausal women, are two difficult problems in obstetrics and gynecology. Hormone therapy, in vitro fertilization and surgical treatments do not completely restore fertility. The advent of hydrogels offers new hope for the treatment of POF and IUA. Hydrogels are noncytotoxic and biodegradable, and do not cause immune rejection or inflammatory reactions. Drug delivery and stem cell delivery are the main application forms. Hydrogels are a local drug delivery reservoir, and the control of drug release is achieved by changing the physicochemical properties, the porous properties and stable three-dimensional structure of hydrogels support stem cell growth and functions. In addition, for POF hydrogels are promising biomaterials for increasing the success rate of ovarian tissue transplantation, and hydrogel-based in vitro three-dimensional culture of follicles drives the development of artificial ovaries. For IUA hydrogels form a barrier at the site of injury and have antibacterial, antiadhesive and antistenosis properties. In this review, we evaluate the physicochemical properties of hydrogels, focus on the latest applications of hydrogels in POF and IUA. We found the limitations on clinical application of hydrogel and provide future prospects.